A Rhaetian microvertebrate fauna from Stowey Quarry, Somerset, U.K. Issue 2 (April 2018) - Cavicchini, Iacopo; Heyworth, H. Cecilia; Duffin, Christopher J.; Hildebrandt, Claudia; Benton, Michael J.
Abstract: Rhaetian bone beds have been described from many locations in south-west England, around Bristol. One site that has never been reported is Stowey Quarry, some 13 km south of Bristol. This quarry yielded Lias, and revealed thin Rhaetian units in the quarry floor, including two bone beds, the basal Rhaetian bone bed, and a second, higher bone bed, also within the Westbury Formation. The fossil fauna of both includes elements typical of Rhaetian bone beds elsewhere, but showing differences in faunal composition between the two. The basal bone bed yielded more specimens and more species, with three taxa ( Sargodon tomicus, Rhomphaiodon minor and Hybodus cloacinus ) exclusive to this bed and eleven identified in total. Severnichthys acuminatus accounts for more than 50% of the countable teeth from the basal bone bed, followed by Gyrolepis albertii with 20%, Lissodus minimus with 14% and Rhomphaiodon minor with 9%. The basal bone bed, as ever, is dominated by chondrichthyans, whereas the upper bone bed is dominated by osteichthyans, which form 90% of the non-dental remains. The only unique taxon is Dapedium, and Gyrolepis albertii is the most abundant species with 45% of countable teeth, followed by S evernichthys acuminatus with 38% and Duffinselache holwellensis with 11%. These faunal differences, and the equally good condition of specimens between both samples confirms that the upper bone bed is independent of the basal bone bed, and is not a reworked subsample.